The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1002/ajmg.b.30336
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional anxiety mediates linkage of GABRA2 haplotypes with alcoholism

Abstract: The GABAAα 2 receptor gene (GABRA2) modulates anxiety and stress response. Three recent association studies implicate GABRA2 in alcoholism, however in these papers both common, opposite-configuration haplotypes in the region distal to intron3 predict risk. We have now replicated the GABRA2 association with alcoholism in 331 Plains Indian men and women and 461 Finnish Caucasian men. Using a dimensional measure of anxiety, harm avoidance (HA), we also found that the association with alcoholism is mediated, or mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 28 publications
(37 reference statements)
7
102
2
2
Order By: Relevance
“…Our previous study in these two populations has shown that alcoholics with high HA, defined as X the population mean (taken as the mean HA for nonalcoholics), and low HA, defined as < the population mean, may be distinct subtypes. 31 In the current study, we only found a nonsignificant trend for the association of HA with GAL haplotypes and diplotypes in alcoholics. Nevertheless, because our study has no precedent, we decided to pursue exploratory analyses of the HA association.…”
Section: Tag Snpscontrasting
confidence: 75%
See 1 more Smart Citation
“…Our previous study in these two populations has shown that alcoholics with high HA, defined as X the population mean (taken as the mean HA for nonalcoholics), and low HA, defined as < the population mean, may be distinct subtypes. 31 In the current study, we only found a nonsignificant trend for the association of HA with GAL haplotypes and diplotypes in alcoholics. Nevertheless, because our study has no precedent, we decided to pursue exploratory analyses of the HA association.…”
Section: Tag Snpscontrasting
confidence: 75%
“…The sample from Helsinki, Finland, has been described in detail elsewhere. 30,31 In total, 514 men were genotyped: 263 alcoholics and 251 nonalcoholics. Written informed consent was obtained according to human research protocols approved by the human research committees of NIAAA and NIMH, NIH, the Department of Psychiatry, University of Helsinki, and the University of Helsinki Central Hospital, Helsinki, Finland.…”
Section: Finnish Caucasiansmentioning
confidence: 99%
“…Another issue may be sexual dimorphism. As described above, Enoch et al (2006) found significant anxiety-mediated GABRA2 haplotype associations with alcoholism in Finnish Caucasian and American Indian men but found no association in American Indian women. The negative study in African Americans (Covault et al, 2008) may be attributable to the fact that in this group the two yin yang risk haplotypes are present at much lower frequencies (29% and 27%) compared with other populations (Enoch, unpublished data; Figure 3).…”
Section: Gaba a Receptor Chromosome 4 Gene Clustermentioning
confidence: 62%
“…Alcoholics, including those with antisocial personality disorder, have been shown to have higher trait anxiety than non-alcoholics (Ducci et al, 2007;Goodwin and Hamilton, 2003). If trait anxiety does indeed play a role in mediating linkage of GABRA2 haplotypes with alcoholism then the Enoch et al (2006) study would predict that COGA alcoholics have higher trait anxiety than the treatment seeking alcoholics of other studies (Covault et al, 2004;Fehr et al, 2006;Lappalainen et al, 2005). Indeed, it has been demonstrated that COGA alcoholics have higher trait anxiety than non-alcoholics (Ducci et al, 2007).…”
Section: Gaba a Receptor Chromosome 4 Gene Clustermentioning
confidence: 99%
See 1 more Smart Citation